Feminine Behavior Management in Personal Selling Activities for Professional Male Makeup Artists - Mulyana, Ahmad; Harbert, Parlin (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: The research aims to describing the phenomenon of makeup artists or male beauty artists in promoting makeup services. They carry out personal selling activities for female customers through managing their feminine behavior. This research used symbolic interactionism theory with phenomenological research methods. It was conducted with qualitative case study method. The data collection technique used observation and in-depth interviews with informants who worked as professional male makeup artists. In addition to obtaining in-depth data, it was also carried out through secondary data for data enrichment so that it could obtain accurate, complete and comprehensive data.